LAPAROSCOPIC ORCHIOPEXY FOR MANAGEMENT OF BILATERAL NON-PALPABLE TESTES; SINGLE CENTER EXPERIENCE - Iqbal, Nadeem; Hasan, Aisha; Saghir, Sumera; Iqbal, Sidra; Saif, Usama bin; Choudhry, Alia Mohsin; Choudry, Ali Mohsin; Gill, Behzad Saeed; Hussain, Ijaz; Iqbal, Daud; Khan, Faheemullah; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2020)
Background: Despite numerous clinical studies regarding the management of unilateral impalpable testes by laparoscopy, there is a paucity of such studies regarding the management of bilateral '˜non-palpable' testes. We shared the outcome of the laparoscopic management of bilateral '˜non-palpable' testes in terms of successful orchiopexy and complications in children. Methods: A total of 22 children underwent bilateral diagnostic laparoscopy for undescended testes who presented to our department from January 2010 till March 2018. We did chart review for variables such as the age of children, operative time, hospital stay, single stage or 2 stage procedure, and operative complications. Preoperatively history and physical examination was done along with baseline investigations and Ultrasound abdomen and scrotum before surgery for general anaesthesia fitness. They were managed by single or two steps laparoscopic orchiopexy according to suitability for each case. Results: We performed bilateral laparoscopic orchidopexies in 22 children having a mean age of 4.1±1.98 years (49.2 months) Mean operative time for single setting bilateral single stage orchiopexy was 136±32 minutes. Out of twenty-two children with bilateral impalpable testes, 12 boys (54.5%) were managed with a single stage Bilateral Laparoscopic technique while the other 10 (45.45%) were managed in 2 staged laparoscopic intervention using Fowler-Stephens technique. Testicular atrophy was seen in 2/44 testes (4.54%). While 1 /44 (2.27%) testis had ascended to the inguinal region requiring redo surgery. Conclusion: Laparoscopic management of bilateral '˜non-palpable' testes in a single or double setting is a safe and effective method of bringing testes down to the scrotum. It has no major morbidities. Keywords: Children; Intra abdominal testis; Laparoscopic Orchidopexy